(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The research aims at introducing accountability creative and the factors influencing or helping to Do in Iraqi companies, was launched two assumptions first that he was effect with significance to a number of factors in the direction of departments in Iraqi companies to practice creative accounting , were selected (9) factors believed to researchers it’s most influential, and second that there importance of significance for a number of ways or methods to prevent or combat creative accounting , and the purpose of testing hypotheses have been designed questionnaire was distributed to a sample of 48 individual practitioners accountable in Iraqi companies and auditors in charge of auditing the accounts of those companies , after analyzing the responses were the most important results that have been reached : • The factors that have been selected as influential their creative accounting application in Iraqi companies have a significant impact morale, and they vary in the degree of impact. • The methods or techniques that have been tested are of significant importance in preventing or moral creative accounting and control can be activated in this area. • There are considerable risks cannot be avoided in the absence of the discovery of creative accounting methods and control.